Mettre en lumière des réseaux invisibles pour les historiens : la bipolarisation d’un réseau aristocratique à la cour de Vienne, 1685-1740 - Éric Hassler (Les Cahiers de Framespa)
The Viennese aristocratic networks appear as such a tangle of individuals and families, that they have never been precisely studied per se, except in relation with political parties. However, the most recent historiography proved that this way of studying the Aristocratic networks was not efficient due to the permanent reconfigurations of political groups depending on circumstances and private interests only. Therefore, it is necessary to find another way of studying networks at the Imperial Court. Putting in graphs the lists of guests at sleigh processions during the winter of 1726, then playing with the scales of the networks (individual, relative, family) reveal aristocratic networks which remain invisible with other kinds of historical sources. In this way, it is possible to re-establish a history of the family and political networks at play at the Court and structuring both nobility and the policy of the Habsburg monarchy during the Modern period.